Pengaruh Kesalahan Dimensi Mesin Cnc Hybrid 3 Axis Terhadap Ketelitian Dan Kepresisian Produk Yang Di Hasilkan - Januardi, M. Ikhsan; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
CNC machines are machine tools that can be operated automatically. Usually a CNC machine can only do one machining process, so it is considered less effective. Based on this, the researchers conducted some research on machine tools capable of carrying out two or more machining processes (CNC Hybrid). In manufacturing CNC Hybrids, one that must be considered is the machine work area and accuracy. In this study, testing was conducted to determine the value of the work area and accuracy of the 3 Axis of CNC Hybrid. Testing is done by making as many as 20 pcs of product samples each. Furthermore, the products are measured to determine the value of the work area and accuracy of the machine. For the 3D printing process the test results are obtained in the form of a work area of 30 cm x 30 cm x 30 cm and a level of accuracy of 0.35 mm and a deviation value of 0.6205 mm. As for the machining process, the accuracy value is 0.45 mm and the repeat value is 18.15375 mm with a deviation of 1.84625 mm.Keywords : CNC, work area, accuracy, precision.